First characterization of PIWI-interacting RNA clusters in a cichlid fish with a B chromosome - Oliveira, Jordana Inácio Nascimento [UNESP] (2022)
Background: B chromosomes are extra elements found in several eukaryote species. Usually, they do not express a phenotype in the host. However, advances in bioinformatics over the last decades have allowed us to describe several genes and molecular functions related to B chromosomes. These advances enable investigations of the relationship between the B chromosome and the host to understand how this element has been preserved in genomes. However, considering that transposable elements (TEs) are highly abundant in this supernumerary chromosome, there is a lack of knowledge concerning the dynamics of TE control in B-carrying cells. Thus, the present study characterized PIWI-interacting RNA (piRNA) clusters and pathways responsible for silencing the mobilization of TEs in gonads of the cichlid fish Astatotilapia latifasciata carrying the B chromosome. Results: Through small RNA-seq and genome assembly, we predicted and annotated piRNA clusters in the A. latifasciata genome for the first time. We observed that these clusters had biased expression related to sex and the presence of the B chromosome. Furthermore, three piRNA clusters, named curupira, were identified in the B chromosome. Two of them were expressed exclusively in gonads of samples with the B chromosome. The composition of these curupira sequences was derived from LTR, LINE, and DNA elements, representing old and recent transposition events in the A. latifasciata genome and the B chromosome. The presence of the B chromosome also affected the expression of piRNA pathway genes. The mitochondrial cardiolipin hydrolase-like (pld6) gene is present in the B chromosome, as previously reported, and an increase in its expression was detected in gonads with the B chromosome. Conclusions: Due to the high abundance of TEs in the B chromosome, it was possible to investigate the origin of piRNA from these jumping genes. We hypothesize that the B chromosome has evolved its own genomic guardians to prevent uncontrolled TE mobilization. Furthermore, we also detected an expression bias in the presence of the B chromosome over A. latifasciata piRNA clusters and pathway genes.